The Mechanisms of Effector Th Cell Responses Contribute to Treg Cell Function: New Insights into Pathogenesis and Therapy of Asthma - Chen, Wenjing; Cao, Yuxue; Zhong, Yuanyuan; Sun, Jing; Dong, Jingcheng (Frontiers in Immunology, 2022)
CD4 + helper T (Th) cell subsets are critically involved in the pathogenesis of asthma. Naive Th cells differentiate into different subsets under the stimulation of different sets of cytokines, and the differentiation process is dominantly driven by lineage specific transcription factors, such as T-bet (Th1), GATA3 (Th2), RORγt (Th17) and Foxp3 (Treg). The differentiation mechanisms driven by these transcription factors is mutually exclusive, resulting in functional inhibition of these Th subsets to each other, particularly prominent between effector Th cells and Treg cells, such as Th2 versus Treg cells and Th17 versus Treg cells. Being of significance in maintaining immune homeostasis, the balance between effector Th cell response and Treg cell immunosuppression provides an immunological theoretical basis for us to understand the immunopathological mechanism and develop the therapy strategies of asthma. However, recent studies have found that certain factor involved in effector Th cells response, such as cytokines and master transcription factors (IL-12 and T-bet of Th1, IL-4 and GATA3 of Th2, IL-6 and RORγt of Th17), not only contribute immune response of effector Th cells, but also promote the development and function of Treg cells, therefore bridging the interplay between effector Th cell immune responses and Treg cell immunosuppression. Although we have an abundant knowledge concerning the role of these cytokines and transcription factors in effector Th cell responses, our understanding on their role in Treg cell development and function is scattered thus need to be summarized. This review summarized the role of these cytokines and transcription factors involved in effector Th cell responses in the development and function of Treg cells, in the hope of providing new insights of understanding the immunopathological mechanism and seeking potential therapy strategies of asthma.